ANALISIS TINGKAT KEMAMPUAN BERPIKIR KREATIF MATEMATIS PESERTA DIDIK DITINJAU DARI GAYA BELAJAR KELAS VII SMP - Purwanti, Dwi; Fakhri, Jamal; Negara, Hasan Sastra (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
This research is motivated by observations at Muhammadiyah junior high school number 3 in Bandar Lampung that ability of students to solve mathematical problems have different thinking skills, diverse learning styles possessed by students in absorbing and processing information while the learning process is taking place and educators have never tested specifically creative thinking and learning styles. The purpose of this research is to determine the level of mathematical creative thinking abilities of students as seen from the visual, auditory and kinesthetic learning styles by Muhammadiyah junior high school number 3 in Bandar Lampung. Subjects for this research were conducted in VIIB and VIIE classes by taking subjects by purposive sampling, namely 2 subjects of visual learning style, 2 subjects in auditory learning styles and 2 subjects of kinesthetic learning styles. The results of this research is to indicate that students with visual learning styles are classified as level 1 (less creative), students with auditorial learning styles are classified as level 1(less creative)  and kinesthetic learning is classified as level 1 (less creative) and as level 3( creative).